Between-study differences in grip strength: a comparison of Norwegian and Russian adults aged 40-69 years - Cooper, Rachel; Shkolnikov, Vladimir M.; Kudryavtsev, Alexander; Malyutina, Sofia; Ryabikov, Andrew; Hopstock, Laila Arnesdatter; Johansson, Jonas; Cook, Sarah Anne; Leon, David; Strand, Bjørn Heine (Journal of Cachexia, Sarcopenia and Muscle, 2021)
Background - Identifying individuals with low grip strength is an initial step in many operational definitions of sarcopenia. As evidence indicates that contemporaneous Russian populations may have lower mean levels of grip strength than other populations in northern Europe, we aimed to: compare grip strength in Russian and Norwegian populations by age and sex; investigate whether height, body mass index, education, smoking status, alcohol use and health status explain observed differences and; examine implications for case-finding low muscle strength. Methods - We used harmonized cross-sectional data on grip strength and covariates for participants aged 40–69 years from the Russian Know Your Heart study (KYH) (n = 3833) and the seventh survey of the Norwegian Tromsø Study (n = 5598). Maximum grip strength (kg) was assessed using the same protocol and device in both studies. Grip strength by age, sex and study was modelled using linear regression and between-study differences were predicted from these models. Sex-specific age-standardized differences in grip strength and in prevalence of low muscle strength were estimated using the European population standard of 2013. Results - Normal ranges of maximum grip strength in both studies combined were 33.8 to 67.0 kg in men and 18.7 to 40.1 kg in women. Mean grip strength was higher among Tromsø than KYH study participants and this difference did not vary markedly by age or sex. Adjustment for covariates, most notably height, attenuated between-study differences but these differences were still evident at younger ages. For example, estimated between-study differences in mean grip strength in fully adjusted models were 2.2 kg [95% confidence interval (CI) 1.4, 3.1] at 40 years and 1.0 kg (95% CI 0.5, 1.5) at 65 years in men (age × study interaction P = 0.09) and 1.1 kg (95% CI 0.4, 1.9) at age 40 years and −0.2 kg (95% CI −0.7, 0.3) at 65 years in women (age × study interaction P < 0.01). Conclusions - We found between-study differences in mean grip strength that ...